Synthesis of Polyhydroxy-2,3-diarylxanthones with potencial antioxidant activity - Santos, Clementina M.M. (2011)
Xanthones are a well-studied class of heterocyclic compounds [1] and over the years these substances have been extensively studied due to their biological properties. Both natural and synthetic derivatives have shown important anti-microbial, anti-tumour, anti-inflammatory as well as antioxidant activities [2]. Several structure/activity studies of polyphenolic compounds revealed that the presence of hydroxyl substituents in certain positions of their skeleton is of great importance for a high antioxidant activity [3]. Taking this knowledge into consideration, we report the synthesis of new polyhydroxy-2,3- diarylxanthones, starting from the 3-bromo-2-methylchromone 1. Aldol condensation of 1 with benzaldehydes leads to the formation of 3-bromo-2-styrylchromones 2 followed by Heck reaction with styrenes to give the 2,3-arylxanthones 3 [4]. The final step consists in the cleavage of protective groups to obtain the desired polyhydroxy-2,3-diarylxanthones 4